Elizabeth Bishop in the Twenty-First Century : Reading the New Editions - Travisano, Thomas, 1951-; Hicok, Bethany, 1958-; Cleghorn, Angus J. (Book collections on Project MUSE., 2012)
"In recent years, a series of major collections of posthumous writings by Elizabeth Bishop--one of the most widely read and discussed poets of the twentieth century--have been published, profoundly affecting how we look at her life and work. The hundreds of letters, poems, and other writings in these volumes have expanded Bishop's published work by well over a thousand pages and placed before the public a "new" Bishop whose complexity was previously familiar to only a small circle of scholars and devoted readers. This collection of essays by many of the leading figures in Bishop studies provides a deep and multifaceted account of the impact of these new editions and how they both enlarge and complicate our understanding of Bishop as a cultural icon."--Project Muse